The Influence Of Giving Benson Relaxation Therapy On Stress Levels In Kidney Failure Patients Undergoing Hemodialysis At Banjarmasin Islam Hospital In 2021 - Linda, Linda; Mariani, Mariani (Sean Institute, 2022)
Chronic Renal Failure (CKD) is a progressive decline in kidney tissue function so that the remaining kidney mass is no longer able to maintain the body's internal environment. Dialysis maintenance includes two main things: hemodialysis (HD) and peritoneal dialysis (PD). As the disease progresses to requiring dialysis, the patient begins to experience several losses: kidney function, leading roles in the family and work, physical function and mobility, tolerance to activities, etc.Hemodialysis takes toxic nitrogenous substances from the patient's blood to the dialyzer to filter and remove toxic metabolic wastes in the body that the kidneys should remove. There are three principles underlying hemodialysis work: diffusion, osmosis, and ultrafiltration. This study aims to determine the effect of Benson relaxation therapy on stress levels in patients with kidney failure undergoing hemodialysis